BERITA KENAIKAN BBM DI MEDIA ONLINE DALAM FRAMING ENTMAN - Zakaria Siregar; Taufik Ilham (Yayasan Formadana Tabagsel Indonesia, 2025)
Framing of fuel hike by online media Waspada.id and Medanbisnisdaily.com This study uses a descriptive qualitative approach that uses a framing analysis model of news text as primary data. In this study, researchers only took 5 (five) news from each media that was considered to have represented other news from each online media, using purposive sampling techniques. The conclusion of the results of research on online media Waspada.id and Medanbisnisdaily.com is seen from the first Entman framing tool to define problems. Online media Waspada.id and Medanbisnisdaily.com both define that the case of fuel increase is an economic problem, but in this case Waspada tends to be more aggressive in reporting the event of fuel increase. In the second Entman tool, estimating the problem or source of the problem (Diagnose cause) the two media put the increase in fuel as the source of the problem in their reporting, while the public was considered as a victim of this event. Third, make moral judgments contained in the news of fuel increases on Waspada, namely that the government is considered not to think about the impact of fuel increases on the community. While in Medanbisnis there are two moral decisions, namely the local government in the North Sumatra region seeks to prevent and overcome the impact of fuel increases. The fourth framing device emphasizes the solution (Treatment recommendation) offered in the news of the fuel increase in Waspada, namely conveying the aspirations of the community to the DPRD RI or the central government. While in Medanbisnis there are two solutions that are emphasized